2014
DOI: 10.4081/ija.2014.567
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertiliser value of digested dairy cow slurry, its liquid and solid fractions, and of dairy cow slurry

Abstract: An understanding of crop availability of livestock slurry nitrogen (N) is necessary to maximise crop N use efficiency and to minimise environmental losses. Results from field and laboratory incubation experiments suggest that first-year crop availability of slurry N comes mainly from its ammonium fraction because net mineralisation of organic N is often negligible in the short term. A two-year field experiment during 2011 and 2012 in northern Italy was undertaken with several aims: to estimate the N fertiliser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Makádi et al (2012) and Šimon et al (2015) confirmed that digestate has high available nutrients profile compared with non-digested, which resulted in significantly increased biomass yields of winter and spring wheat. Furthermore, it has been reported in several studies that the crop N uptake is higher with all types of digestate than non-digested manure if N losses by volatilization and leaching are prevented (Cavalli et al, 2014;Gunnarsson et al, 2010;Loria et al, 2007;Odlare et al, 2008). Moreover, humic acids in digestate are one of the most important organic fertilizers that increase N uptake and plant growth (Tahir et al, 2011).…”
Section: Root Straw Ears and Total Biomassmentioning
confidence: 99%
“…Makádi et al (2012) and Šimon et al (2015) confirmed that digestate has high available nutrients profile compared with non-digested, which resulted in significantly increased biomass yields of winter and spring wheat. Furthermore, it has been reported in several studies that the crop N uptake is higher with all types of digestate than non-digested manure if N losses by volatilization and leaching are prevented (Cavalli et al, 2014;Gunnarsson et al, 2010;Loria et al, 2007;Odlare et al, 2008). Moreover, humic acids in digestate are one of the most important organic fertilizers that increase N uptake and plant growth (Tahir et al, 2011).…”
Section: Root Straw Ears and Total Biomassmentioning
confidence: 99%
“…Laboratory and field experiments have been carried out with digestate in order to investigate N uptake of plants as well as the effect on soils regarding N mineralization, and often compared with mineral N fertilizers as control [19][20][21][22][23][24][25][26][27][28][29]. Other investigations focused on solid and liquid fractions of separated digestate regarding their use as fertilizer [12,[30][31][32][33]. Further studies show that digestate can also improve soil quality and water holding capacity on marginal soils [34] and that the use of fermentation residues is beneficial for selected plants such as tomato, pepper, kohlrabi or ornamentals.…”
Section: Introductionmentioning
confidence: 99%
“…; Cavalli et al. ), the mineralization of the organic N can become non‐negligible over the long term (Gutser et al. ; Schröder et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, the agronomic distinction between 'organic' (manure) and 'mineral' (industrial) fertilizers is misleading, since liquid manure contains high proportions of inorganic compounds, especially ammonium and phosphate, and easily mineralized soluble organic compounds, such as urea. Therefore, both industrial fertilizers and liquid manure present a high proportion of inorganic N available for plants in the short term (Muñoz et al 2004;Cavalli et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation